2012
DOI: 10.1123/ijsnem.22.6.430
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Quercetin Supplementation on Markers of Muscle Damage and Inflammation after Eccentric Exercise

Abstract: The flavonoid quercetin is purported to have potent antioxidant and anti-inflammatory properties. This study examined if quercetin supplementation attenuates indicators of exercise-induced muscle damage in a double-blind laboratory study. Thirty healthy subjects were randomized to quercetin (QU) or placebo (PL) supplementation and performed 2 separate sessions of 24 eccentric contractions of the elbow flexors. Muscle strength, soreness, resting arm angle, upper arm swelling, serum creatine kinase (CK) activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 25 publications
4
47
2
Order By: Relevance
“…Corroborating, quercetin co-ingested with other flavonoids and food components prevents inflammation in trained cyclists 3 days after exercise [16] and confers myocardium protection against intense exercise injury [20]. On the other hand, quercetin did not reduce blood oxidative stress and inflammation or muscle inflammation and damage in post-exercise during clinical trials possibly due to high dose treatment during a long period [14,15,17,19]. Therefore, whether quercetin has beneficial effects in muscle inflammation and oxidative stress is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Corroborating, quercetin co-ingested with other flavonoids and food components prevents inflammation in trained cyclists 3 days after exercise [16] and confers myocardium protection against intense exercise injury [20]. On the other hand, quercetin did not reduce blood oxidative stress and inflammation or muscle inflammation and damage in post-exercise during clinical trials possibly due to high dose treatment during a long period [14,15,17,19]. Therefore, whether quercetin has beneficial effects in muscle inflammation and oxidative stress is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, polyphenol supplementation has been demonstrated to reduce force deficits and markers of muscle damage in response to resistance exercise (Panza et al 2008;Jowko et al 2011), while others have demonstrated equivocal results (Paulsen et al 2014). Although supplementation with antioxidants (vitamins A, C, and E) appear to blunt the response of the proinflammatory cytokines following endurance exercise (Vassilakopoulos et al 2003), the benefits of polyphenol supplementation in conjunction with eccentric exercise have been ambiguous (Kerksick et al 2010;O'Fallon et al 2012;Herrlinger et al 2015). Decreases in circulating neutrophil counts have been observed following eccentric exercise in conjunction with epigallocatechin gallate (EGCG) supplementation (Kerksick et al 2010), though the fate of these cells is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the fact that there appears to be no completely effective treatment for preventing/reducing EIMD and treating DOMS [1,6], the use of complimentary therapy, in particular nutraceuticals (e.g. tart cherry juice [9], curcumin [10], and quercetin [11]) that possess anti-inflammatory properties and have the potential to attenuate EIMD-induced oxidative stress, have become of interest [1]. …”
Section: Introductionmentioning
confidence: 99%